IMPLEMENTASI KODE ETIKA ENGINEERING DALAM PROSES PROYEK INFRASTRUKTUR - Edison Hatoguan Manurung; Faredzi Dhika Saputra (SINERGI : Jurnal Riset Ilmiah, 2026)
Engineering code of ethics serves as a fundamental moral framework that every engineer must uphold throughout the infrastructure project process. This study aims to analyze the implementation of engineering codes of ethics in infrastructure project processes, identify the challenges encountered, and formulate strategic recommendations to enhance professional ethical compliance in the field. The method employed is a literature review and qualitative analysis of various infrastructure project cases in Indonesia. The results indicate that adherence to the ASCE (American Society of Civil Engineers) Code of Ethics and the Indonesian Engineer Code of Ethics (PII) is still inconsistently applied in practice, particularly regarding public safety, professional integrity, and environmental sustainability. Economic pressures, tight project schedules, and weak oversight are identified as the main barriers. This study recommends strengthening ethics education in civil engineering curricula and enforcing stricter sanctions against code of ethics violators.